Epidemiological Features of HPV-Associated Cancer in situ of Various Localization - D. V. Kholopov; L. V. Lyalina; V. V. Khizha; E. E. Topuzov; T. G. Zadorkina (Эпидемиология и вакцинопрофилактика)
Relevance. In Russia and abroad, the incidence of cancer in situ (CIS) of the breast and cervix is most widely represented, the epidemiological features of this neoplasia of other localizations have not been studied sufficiently. Among them, a significant place is occupied by a group of malignant neoplasms in situ associated with the human papillomavirus (HPV), which have common etiopathogenetic mechanisms of development.The aim of the study was to determine the structure, as well as the incidence and mortality rates from HPV-associated cancer in situ among the population of St. Petersburg.Material and methods. The research materials included cases of cancer in situ of the oral cavity, pharynx, larynx, anal canal, vulva, vagina, cervix and penis in St. Petersburg in the period 2001 –2023. The calculation of the indicators was carried out according to the data of form No. 7 «Information on malignant neoplasms» and archival materials of the Population Cancer Registry of St. Petersburg. The analysis included 1952 cases of the disease and 50 deaths from malignant neoplasms, initially registered as cancer in situ. Research methods: retrospective epidemiological analysis and statistical methods.The results of the study. In the structure of in situ cancer associated with HPV, among the male population, the largest proportion was occupied by CIS of the larynx and penis (36.4% each), among the female population – cervix (94.9%). The average long-term incidence of cancer in situ of the oral cavity, pharynx, larynx, anal canal, vagina and penis was less than 0.1 per 100 thousand of the population with the maximum incidence in the age group of 50-69 years. From 2001 to 2023 in St. Petersburg, the incidence of cervical CIS decreased significantly from 6.86 to 1.17 per 100 thousand. the female population (p = 0.001), while since 2004, the highest incidence rate has been recorded annually in the 30 –39 age group. From 2001 to 2023, 11 cases (31.4% of all CIS localities) among males and 39 cases (27.7% of all CIS cases) among the female population became the cause of death from HPV-associated ZNO, initially registered as cancer in situ of the corresponding localizations.Conclusion. As a result of the study, epidemiological features of morbidity and mortality from HPVassociated cancer in situ of various localization in the conditions of St. Petersburg were established.